ANALISA PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN SOMBA OPU KABUPATEN GOWA DENGAN ANALISIS LINEAR SEDERHANA - Ratih Suwanti; Muh. Asdar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
Employee performance is a crucial factor in achieving effective public service and organizational goals. Work discipline is considered one of the key determinants influencing employees' productivity and responsibility in carrying out their duties. This study aims to examine the effect of work discipline on employee performance at the Somba Opu District Office, Gowa Regency. A quantitative research approach with a survey method was employed. The study involved all 56 employees as respondents using a census sampling technique. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed using descriptive statistics and simple linear regression with the assistance of SPSS software. The findings reveal that work discipline has a positive and statistically significant effect on employee performance. The regression analysis indicates a significant relationship (p < 0.05), while the coefficient of determination (R² = 0.808) demonstrates that work discipline explains 80.8% of the variance in employee performance. These findings suggest that improving employees' adherence to organizational rules, punctuality, responsibility, and commitment to work can substantially enhance overall performance. Therefore, strengthening work discipline should be considered a strategic priority for improving the quality of public services within government institutions.